Three Doctrines of the Nature of Mathematics (Some Comments of a Knowledge Theorist) - Wójcicki, Ryszard (Bulletin of the Section of Logic, 2017)
In this note I am reflecting on interrelations between three concepts of truth: (1) that employed by Hilbert arguing his formalist view on the nature of mathematics, (2) Freges idea of truth supported by mathematical intuition, and (3) known as Aristotelian correspondence idea of truth concerning any propositions not merely mathematical.